From immunological mechanisms to targeted therapies: a bibliometric analysis of vitiligo treatment research (2005–2025) - Luo, Longfei; He, Xiaolei; Shi, Ying (Frontiers in Immunology, 2026)
BackgroundVitiligo is a chronic autoimmune disorder characterized by CD8+ T cell-mediated destruction of melanocytes. It affects up to 2% of the global population and has a profound psychosocial impact. Over the past two decades, advances in understanding immunological mechanisms, particularly IFN-γ signaling and JAK-STAT pathway dysregulation, have reshaped therapeutic approaches from empirical regimens to targeted immunomodulatory interventions.ObjectiveTo analyze global vitiligo treatment research trends from 2005 to 2025, examining publication patterns, collaboration networks, and the evolution of therapeutic strategies.MethodsPublications related to vitiligo treatment were retrieved from the Web of Science Core Collection (WoSCC) and analyzed using R (Bibliometrix), VOSviewer, and CiteSpace. Scopus database was used for supplementary validation of major trends. In parallel, randomized controlled trials (RCTs) were systematically identified from PubMed to contextualize clinical research.ResultsIn total, 3, 483 publications were included in this study. Annual output increased at a compound growth rate of 7.27%. China, the United States, and India were the leading contributors, whereas the Egyptian Knowledge Bank and Harvard University were the most productive institutions. Thematic analysis revealed a gradual transition from traditional therapies such as corticosteroids and phototherapy to immune-targeted strategies. Citation bursts highlight the emergence of JAK inhibitors and biologics. Network analyses revealed fragmented author clusters, but strong international collaborations, particularly in Europe. An analysis of 249 RCTs revealed that pharmacological therapies, surgical interventions, and phototherapy constitute the three major research themes. Immunomodulatory therapies, particularly JAK inhibitors, such as ritlecitinib, have emerged as a key focus in ongoing clinical trials.ConclusionThis multi-database analysis delineates the evolving landscape of vitiligo treatment research, characterized by expanding output and increasing focus on immune-targeted therapies. Persistent gaps in clinical evidence, especially regarding long-term outcomes and pediatric populations, underscore the need for continued high-quality clinical studies in this field.